Effect of a resonant suspended ceiling on the acoustic properties of a hall / Rezonansinių kabamųjų lubų įtaka salės akustiniams rodikliams - Stauskis, Vytautas (Journal of Civil Engineering and Management, 1996)
The article covers the experimental research into basic acoustic properties of a hall using a new type resonant suspended ceiling with large area cross-shaped apertures between surfaces. The research was carried out at a physical simulator of a hall. Geometric parameters, frequency range of the simulator and availability of technical equipment were taken into consideration while selecting the scale of the simulator. A recording hall of the Lithuanian radio and TV’s Grand Symphonic Orchestra was chosen for the purposes of research. The dimensions of the hall are 34×22×12.7 m. The scale of a simulator for such a large hall was established as 1:25. All the wall and floor surfaces of the simulator are made of textolite. Its coefficient of sound absorption at 10 kHz is equal to 0.15. The suspended ceiling is made of 6 mm thick plywood whereof all the contours had been lacquered 3 times. The orchestra’s raised platform of 116 m2 floorspace was covered with 5–6 mm thick flannel which has coefficient of absorption of about 0.5–0.6. In this case the absorption of sound in the air and characteristics of materials are of no importance, as all the research results are relative. A block diagram was used for recording of sound signals at the simulator which diagram comprised a sound source, microphone, microphone’s amplifier and analog-to-digital converter. A spark impulse was used as a sound source which impulse was formed by our made spark generator with preset necessary technical parameters. The research was carried out using a 1/4” microphone. An analog-to-digital converter had been manufactured according to preset characteristics. It was designed for changing analog signals into digital form for their further processing. The number of input channels can be set up from 1 through 8. The nominal level of the input signal is ± 1 V. The converter’s discrimination is equal to 12 bits. Time of conversion is 2 μs. The quantization time is equal to 5 μs, whereas the quantization frequency is 200 kHz. The experimental simulator of a hall allows to determine the dependence of basic acoustic characteristics on the form of the apertures in the suspended ceiling, their surface, distance to the hard surface, absorbing material used in side and end walls and over the suspended ceiling, as well as on the distance from the source to the microphone. The research covered by this article determines the effect produced upon the acoustic coefficient by the distance between the suspended ceiling and the hard surface while the area of the cross-shaped aperture is not changed. During the research a measurement point was chosen near the sound source. The influence of the height of the suspended resonant ceiling upon the reverberation time is expressed only up to 160 Hz, however, a more expressive dependence has not been noticed. The decrease in the reverberation time at this range reaches 0.4–0.6 s. At frequencies of 200 and 250 Hz an expressly noticeable resonance is formed at which resonance the reverberation time is reduced even by 1.1 s., which is a large figure. Under further increase in the frequency the decrease is stable and reaches about 0.4 s. Such a decrease in the reverberation time with the expressive resonance at 200–250 Hz is dependent only on the crossshaped apertures in the suspended ceiling. This indicates that they have effect on the hall’s acoustics.The decrease in the early reverberation time is most expressive at very low frequency up to 100 Hz and it reaches even 1–7 s. Resonance occurs again at 200 Hz, at which resonance the reverberation is decreased by up to 2.5 s and is not dependent on the height of the suspended ceiling. The early damping period of the sound field is basically dependent on the early sound reflections. They are of crucial importance while forming the subjective perception of a sound. The coefficient of the sound absorption depends on the height of the suspended ceiling and it is higher when the height of the ceiling is reduced. In all cases this coefficient has a resonant importance at 200–250 Hz. The coefficients of the absolute absorption are reduced because there is an increased reverberation time of the entire hall and surface area. The sound absorption is expressly increased only when the distance between the height of the suspended ceiling and the hard surface is 100 cm. At resonant frequencies of 200 and 250 Hz it is equal to 60 m2. The fidelity index of music is changeable from −14 dB at lower frequencies up to 0 dB at higher frequencies. The increase in the height of the suspended ceiling begins to have effect only from 200 Hz. Article in Lithuanian. First Published Online: 26 Jul 2012